EFL Teacher's Perception on Reading Strategies Taught in High Schools - Dian Indrianis Fitri; Daniel Ginting (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2021)
While reading activity is a complex phenomenon, recent research on reading strategies has not provided comprehensive explanation of the role and perceptions of teachers regarding appropriate reading strategies helping students with learning difficulties. This paper is aimed to provide a sketch of the teacher's views and strategies to facilitate students with appropriate reading strategies.  EFL teachers have different kinds of reading strategies applied in the classrooms.  This study has found that three groups of teachers teaching in excellent accredited public schools, good accredited public school and very good Islamic private school use various strategies during the teaching of reading. Teachers' perceptions on the teaching of reading strategies are closely related to their readiness with knowledge about reading strategies, students' reading problems and their belief. This study suggests that EFL teachers and future researchers need to continuously investigate effective teaching of reading skill in relation to students' reading strategies.